Early maternal‐newborn contact and positive birth experience. Issue 1 (24th August 2018) - Brubaker, Laura H.; Paul, Ian M.; Repke, John T.; Kjerulff, Kristen H.
Abstract: Background: In recent years, there has been increasing recognition of the importance of early maternal‐newborn contact for the health and well‐being of the newborn and promotion of breastfeeding. However, little research has investigated the association between early maternal‐newborn contact and the mother's birth experience. Methods: As part of a large‐scale prospective, cohort study (the First Baby Study [FBS]), nearly 3000 women who delivered in Pennsylvania (2009‐2011) reported how soon after delivery they first saw, held, and fed their newborns. Birth experience was measured via telephone interview 1 month postpartum, using the FBS Birth Experience Scale, a 16‐item scale which addresses women's feelings about the delivery. General linear models were used to measure associations between time to first maternal‐newborn contact and birth experience, controlling for relevant confounders, including maternal age, race/ethnicity, insurance coverage, delivery mode, gestational age, and pregnancy and delivery complications. Results: The sooner that new mothers first saw, held, and fed their newborns after delivery the more positive their childbirth experiences (all P ‐values < 0.001). Women who delivered by cesarean were less likely to see, hold and feed their newborns shortly after delivery than those who delivered vaginally (all P ‐values < 0.001), and reported less positive birth experiences ( P < 0.001). However, if they first saw, held, and fed their newborns shortly after delivery, they reported more positive birth experiences than those who delivered vaginally ( P = 0.010). Discussion: Early maternal‐newborn contact after delivery was associated with positive birth experiences for new mothers, particularly those who delivered by cesarean.